Examination of Temporary Shelter Areas of the Eastern Black Sea Part - Fatma Berfin Abanoz; Nilhan Vural (Doğal Afetler ve Çevre Dergisi)
With the deterioration of the natural ecosystem of our world, the experience of climate changes and the unconscious consumption of natural resources, many negative situations have occurred on the natural environment. The frequency of occurrence of natural disasters, which is one of these deficiencies, their severity and the damage they cause to both the natural environment and society have increased. As a result of this situation, disaster management and implementation processes were re-planned on the basis of both the unit and the society, and more applicable and usable studies were put forward. Temporary shelter areas, which constitute a step of this process, are important for disaster victims to continue their lives in a healthy and comfortable way, especially after natural disasters occur, and also to partially return to their old living patterns both physically and psychologically. Within the scope of this study, temporary shelter areas which determined by the Eastern Black Sea Part Provincial Disaster and Emergency (AFAD); were evaluated in terms of basic features, transportation, security and user. In the study, it is aimed to analyze the deficiencies of temporary shelter areas in the provinces of Artvin, Rize, Trabzon, Bayburt, Gümüşhane, Giresun and Ordu, which constitute the Eastern Black Sea Part, and to plan these areas depending on the requirements and standards for providing a contribution for further researches.